2006
DOI: 10.1002/em.20272
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induced in human peripheral blood lymphocytes by industrial solid waste and municipal sludge leachates

Abstract: Exposure of humans to toxic compounds occurs mostly in the form of complex mixtures. Leachates, consisting of mixtures of many chemicals, are a potential risk to human health. In the present study, leachates of solid wastes from a polyfiber factory (PFL), an aeronautical plant (AEL), and a municipal sludge leachate (MSL) were assessed for their ability to induce DNA damage in human peripheral blood lymphocytes using the alkaline Comet assay. The leachates also were examined for their physical and chemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 55 publications
(55 reference statements)
1
30
0
Order By: Relevance
“…The amount of DNA damage (measured by the comet tail length) was normalized to untreated controls, resulting in a DNA damage index (IDD). 34 Measurements of 50 different cells from two separate slides at each concentration for each metal were performed with a public domain image analysis program for the single cell electrophoresis (comet) assay.…”
Section: Dna Damage: Single Cell Electrophoresis (Comet Assay)mentioning
confidence: 99%
“…The amount of DNA damage (measured by the comet tail length) was normalized to untreated controls, resulting in a DNA damage index (IDD). 34 Measurements of 50 different cells from two separate slides at each concentration for each metal were performed with a public domain image analysis program for the single cell electrophoresis (comet) assay.…”
Section: Dna Damage: Single Cell Electrophoresis (Comet Assay)mentioning
confidence: 99%
“…Aquatic animal assay using goldfish (Carassius auratus) also indicates that raw landfill leachate induced DNA damage in peripheral erythrocytes, and increased the frequency of micronucleus (MN) in gill cells [4]. Investigation on mammals shows that both municipal landfill leachate and industrial solid waste leachate could cause the increase of MN and chromosomal aberration (CA) frequency, and contribute to the formation of DNA damage in mouse bone marrow and blood cells in vivo [5][6][7], and may be responsible for the DNA damage in human peripheral blood lymphocytes [8]. The cytogenetic abnormalities and DNA damage induced by landfill leachate implicate that humans consuming leachate contaminated water are at increased risk of developing adverse health consequences.…”
Section: Introductionmentioning
confidence: 97%
“…The waste pose serious hazard to human health and environment if improperly stored, treated, transported, disposed off or managed (Misra et al, 2005). Small amount of leachate can pollute large amount of groundwater posing serious health hazard due to consumption of such contaminated water (Bakare et al, 2007). In several earlier studies, it has been observed that all of the Indian cities dispose their waste in few kilometer distances from the city in open dumping places without having concept of scientific techniques of landfilling and about its impact on human health.…”
Section: Introductionmentioning
confidence: 99%